Reflexos da clarificação do caldo de cana com moringa sobre compostos inorgânicos do açúcar VHP - Costa, Gustavo H. G. [UNESP]; Masson, Igor S. [UNESP]; Freita, Lidyane A. de [UNESP]; Roviero, Juliana P. [UNESP]; Mutton, Marcia J. R. [UNESP] (Univ Federal Campina Grande, 2015)
The aim of this study was to determine the effects of sugarcane juice clarification, using extract of leaves and seeds of moringa (Moringa oleifera Lamarck) as auxiliary sedimentation, on the concentration of inorganic compounds of clarified juice and sugar VHP (Very High Purity - Export Type). The experimental design used was a 5 x 2 factorial arrangement with four replications. The performed main treatments included the extracted original sugarcane juice, the synthetic polyelectrolyte, the leaf and seed extract, and a control. The secondary treatments consisted of the sugarcane varieties RB92579 and RB867515. The sugarcane juice was clarified by simple defecation, evaporated until 60 degrees Brix and subjected to a cooking process. In the original juice, in the clarified juice and in the produced sugar the phosphorus, potassium, calcium, sodium, magnesium, manganese, iron and total ashes contents were quantified. The use of extract of leaves and seeds of moringa was effective on juice treatment destined to sugar production, as they removed high quantities of calcium and iron compared to the synthetic polymer. The extract of leaves was the better auxiliary in sedimentation when compared to the others.

Objetivou-se, neste trabalho, avaliar os reflexos da clarificação do caldo de cana utilizando extrato de folhas e sementes de moringa (Moringa oleifera Lamarck) como auxiliares de sedimentação sobre os teores dos compostos inorgânicos do caldo clarificado e do açúcar VHP (Very High Purity - Tipo Exportação) produzido. O delineamento experimental utilizado foi o fatorial 5 x 2 com quatro repetições; o primeiro fator correspondeu aos auxiliares de sedimentação: extrato de folhas e sementes de moringa, polieletrólito sintético e testemunha; já o segundo fator correspondeu a duas variedades de cana-de-açúcar: RB92579 e RB867515. O caldo extraído foi clarificado através de caleagem simples, concentrado até 60 oBrix e submetido ao processo de cozimento. No caldo original, clarificado e no açúcar produzido, foram quantificados os teores de fósforo, potássio, cálcio, sódio, magnésio, manganês e ferro além do teor de cinzas totais. Os empregos dos extratos de folhas e sementes de moringa se mostraram eficazes no tratamento do caldo destinado à produção de açúcar, por eliminar quantidades significativas de cálcio e ferro em comparação ao polieletrólito sintético. O extrato de folhas foi o melhor auxiliar de sedimentação,quando comparado aos demais.
Reflects of clarification of sugarcane juice with moringa on inorganic compounds of sugar VHP
Keywords: Simple defecation; Polyelectrolyte; Sucroenergetic sector; Crystallization; Sugar specification